2018
DOI: 10.4236/jbm.2018.610006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Helicobacter pylori</i> and the Interest of Its Eradication during the Functional Dyspepsia

Abstract: Functional dyspepsia constitutes by its impact in quality of life and socioeconomic impact areal public health problem (40% of the adult population in the Western world). The prevalence of infection with Helicobacter pylori (HP) in patients with functional dyspepsia is about 30%-70%. The aim of our study is to observe the improvement of functional dyspepsia (FD) after Helicobacter pylori (HP) eradication. Methods: This is a prospective study over a period of 68 months (May 2009-January 2015). We included all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It is estimated that over 3 billion people worldwide are infected with H. pylori , with the majority of cases found in developing countries [ 8 ]. Epidemiological studies report the prevalence of H. pylori infection in individuals with functional dyspepsia to range from approximately 30% to 70% [ 9 ]. Despite some controversy, previous clinical findings have shown that eradicating H. pylori leads to symptom improvement in about 70% of infected patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over 3 billion people worldwide are infected with H. pylori , with the majority of cases found in developing countries [ 8 ]. Epidemiological studies report the prevalence of H. pylori infection in individuals with functional dyspepsia to range from approximately 30% to 70% [ 9 ]. Despite some controversy, previous clinical findings have shown that eradicating H. pylori leads to symptom improvement in about 70% of infected patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%